Penegakan Hukum Lingkungan Dalam Bisnis Berkelanjutan - Cokorda Istri Ratih Laksmi Dewi; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2024)
Law No. 24 of 1992 was enacted to effectively manage natural resources on land, sea and air in a sustainable manner. The aim is to promote sustainable development through dynamic spatial planning and environmental conservation. The problems are: 1) How is environmental law enforcement in sustainable business strategy? And 2) What are the sanctions for companies that violate the environment? This research uses normative research methods. The Job Creation Law aims to address pollution problems and encourage environmentally friendly practices in the business sector. Environmental law enforcement in this sustainable business is set to prevent companies from exceeding acceptable limits in releasing substances or energy into the environment. This law provides penalties for environmental violations, with priority on administrative sanctions, civil liability for compensation and environmental restoration, as well as criminal law specifically for serious violations that have a major social and environmental impact.